2019
DOI: 10.1016/j.celrep.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Cells Restrict MCMV and Drive Stress-Induced Extramedullary Hematopoiesis through STAT1

Abstract: SUMMARY Cytomegalovirus (CMV) has a high prevalence worldwide, is often fatal for immunocompromised patients, and causes bone marrow suppression. Deficiency of signal transducer and activator of transcription 1 (STAT1) results in severely impaired antiviral immunity. We have used cell-type restricted deletion of Stat1 to determine the importance of myeloid cell activity for the defense against murine CMV (MCMV). We show that myeloid STAT1 limits MCMV burden and infection-associated pathology in the spleen but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 87 publications
(113 reference statements)
0
10
0
Order By: Relevance
“…This ambiguity might be dependent on the context of infection or on the specific monocyte subpopulation. Whereas Ly6C - CX3CR1 hi patrolling monocytes are involved in dissemination ( 32 ), Ly6C + CCR2 + inflammatory monocytes can engage antiviral responses in early infection via direct or indirect mechanisms ( 33, 34, 38, 80, 83 ). Ly6C + CCR2 + inflammatory monocytes could initiate differentiation of memory CD8 + T and NK cells into antimicrobial effector cells ( 33 ) or showed direct iNOS-mediated antiviral effects ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This ambiguity might be dependent on the context of infection or on the specific monocyte subpopulation. Whereas Ly6C - CX3CR1 hi patrolling monocytes are involved in dissemination ( 32 ), Ly6C + CCR2 + inflammatory monocytes can engage antiviral responses in early infection via direct or indirect mechanisms ( 33, 34, 38, 80, 83 ). Ly6C + CCR2 + inflammatory monocytes could initiate differentiation of memory CD8 + T and NK cells into antimicrobial effector cells ( 33 ) or showed direct iNOS-mediated antiviral effects ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the myeloid STAT1 deletion model, the ability to combat early MCMV infection correlated with the ability to mount extramedullary hematopoiesis ( 38 ). In this study we have specifically investigated the role of emergency hematopoiesis on MCMV infection under leukopenic conditions and report that M-CSF-induced myelopoiesis promotes rapid reconstitution of antiviral activity and protection from infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed an increase in TER119 + cells indicating the activation of extramedullary hematopoiesis, as was described after stimulation with TLR7 and TLR9 ligands as well as after infection with bacteria ( Salmonella spp ., Ehrlichia spp .) and virus (mouse cytomegalovirus) ( 19 , 21 – 23 , 38 40 ). Subsequently, we found that TER119 was also detectable on the surface of a small proportion of CD11c high cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, inflammatory activation of the hematopoietic system is not limited to the bone marrow, but certain infections can induce the egress of early progenitor cells from the bone marrow to the spleen or expand spleen-resident progenitor cells to allow for extramedullary hematopoiesis ( 18 20 ). Extramedullary hematopoiesis critically depends on the presence of macrophages, on activation of pattern recognition receptors such as Toll-like Receptor 9 (TLR9), on MyD88/TRIF signaling and on STAT1 expression in myeloid cells, and is characterized by accumulation of TER119 + cells of the red blood cell lineage in the spleen ( 19 , 21 – 23 ). Of note, certain pathogens suppress extramedullary hematopoiesis as part of their immune evasion program ( 19 ), indicating an important role for this phenomenon in the innate immune defense.…”
Section: Introductionmentioning
confidence: 99%